Modeling of tunneling spectroscopy in high- Tc superconductors - Shukrinov, Yu. M.; Namiranian, A.; Najafi, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The tunneling density of states of high-Tc superconductors is calculated taking into account the tightbinding band structure, group velocity, and tunneling directionality for s-wave and d-wave gap symmetry. The characteristic density of states has asymmetry of the quasiparticle peaks, flat s-wave and cusplike d-wave subgap behavior, and an asymmetric background. We consider that the underlyingasymmetry of the conductance peaks is primarily due to the features of the quasiparticle energy spectrum, and the d-wave symmetry enhances the degree of asymmetry of the peaks. Increasing the lifetime broadening factor changes the degree of asymmetry of the tunneling conductance peaks andleads to confluence of the quasiparticle and van Hove singularity peaks.